Klasifikasi Jenis Tanah di Kota Bengkulu Berdasarkan Metode Horizontal To Vertical Spectra Ratio - Istofiyah, Istofiyah; Supriyadi, Supriyadi; Adhi, M. Aryono; Setyo Rahman, Aditya; Pramono, Sigit; Sativa, Oriza; Yudhi Octantyo, Ardian; Fani Habibah, Nur (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
Bengkulu City is one of the regions in Indonesia with a high level of earthquake susceptibility. To understand the seismic characteristics of the soil in this area, this study employs the Horizontal-to-Vertical Spectral Ratio (HVSR) method based on microtremor data to identify the dominant frequency (F0) and amplification factor (A0), which play a crucial role in seismic microzonation analysis. This study collected 143 microtremor measurement points distributed across Bengkulu City, which were analyzed using Geopsy software to obtain dominant period (Tdom) values and classify soil types. The analysis results indicate that the dominant period values in Bengkulu City range from 0.09213 s to 0.722799 s, reflecting variations in soil characteristics across the region. Overall, Bengkulu City is predominantly composed of medium to hard soil, with most areas such as Pondok Kelapa, Muara Bangka Hulu, the southern part of Sungai Serut, Selebar, and Kampung Melayu classified as medium soil. Meanwhile, hard soil to bedrock classifications are found in Teluk Segara, Ratu Samban, Ratu Agung, Singaran Pati, and the southeastern part of Muara Bangka Hulu, which are dominated by the Alluvium and Terrace Alluvium formations. Additionally, soft soil areas are located in the central part of Sungai Serut, influenced by their proximity to water bodies such as lakes and swamps. These findings confirm that areas with soft soil have a higher potential for seismic amplification, making them more vulnerable to earthquake shaking. Therefore, the results of this study are expected to serve as a reference for disaster mitigation, particularly in earthquake-resistant infrastructure planning and construction in Bengkulu City. Keywords: HVSR, Dominant period, Amplification